Political investment in economic protection a note - Balisacan, Arsenio M. (Philippine Review of Economics and Business (formerly The Philippine Review of Business and Economics), 1987)
This note presents some aspects of the neoclassical economy of economic protection. It develops a conceptual framework which focuses on the costs and benefits of investment in political influence to certain coalitions in the society and how the benefit-cost structure may affect the level of economic protection and the amount of what Bhagwati called "directly unproductive profit-seeking" activities.